Enchancing QoS protection in MPLS networks - Hanshi, Sabri M.; Al-Khateeb, Wajdi Fawzi Mohammed (2010)
MPLS recovery mechanisms are increasing in popularity because they can guarantee fast restoration and high QoS assurance. In fact, QoS is important for interactive voice and video application and for specific clients. However, link failure always incurs delay and packet losses of the traffic passing through the failed link. Therefore, network has to restore the traffic by switching the affected traffic to alternative path. In this paper, QoS objectives are concerned in this study to redirect the protected traffic with acceptable levels of quality before failure take place. The proposed scheme setup more than one alternative path in advance in order to introduce fast rerouting and the selecting criteria is based on the required bandwidth and end-to-end delay. In this work, we proposed the traffic splitter to split the protected traffic after failure, in case the available bandwidth in the alternative path is not enough to deliver the traffic. Finally, alternative path selection is updated based on current network resource availability. To verify the efficiency of the proposed algorithm, the MPLS network simulator MNS-2 has been used as the test platform.